HUBUNGAN KETUBAN PECAH DINI DENGAN KEJADIAN KALA II LAMA PADA IBU BERSALIN - Hilyati, Hesti Via; Wahyuningsih, Sri; Widayati, Agustina (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Premature rupture of membranes is rupture of membranes before signs of labor. Premature rupture of membranes causes prolonged labor. This study used an observational analytic design with cross sectional approach, data were taken from medical records and observation sheets in delivery room at the Edifuz Clinic SP.OG Lumajang which was held in August 2022 with population are 50 mothers and sample are 40 respondents using Simple Random Sampling technique. Data collection includes coding, editing and tabulation. Data were analyzed by computer using the chi-square test. The results showed that the majority premature rupture of membranes in Edifuz Clinic SP.OG Lumajang of 2022 experienced PROM (65%). The incidence of long second stage at the Edifuz Clinic SP.OG Lumajang in 2022 almost all experienced incidence of long second stage (67.5%). There is a relationship between premature rupture of membranes and incidence of long second stage at the Edifuz Clinic, SP.OG Lumajang in 2022. The results analysis with the chi-square test show the P-value = 0.001 < 0.05, meaning that there is relationship between premature rupture of membranes and incidence of long second stage. In this study, there is a relationship between premature rupture of membranes and incidence of second stage of labor. The suggestion put forward is research sites should provide information related to early detection of high-risk pregnancies through provision of leaflets so that they can increase public knowledge, especially about premature rupture of membranes.